Evaluation of Implementation of Face-to-Face Lectures Limited to Table Tennis and Aquatic I Courses - Maria Andriani Barek Ladjar; Veramyta M.M. Flora Babang; Ronald Dwi Ardian Fufu; Jurdan Martin Siahaan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The purpose of this study was to evaluate the implementation of limited face-to-face lectures for Table Tennis and Aquatics I. The study was conducted on students of the Physical Education Study Program FKIP in semester 4 of the even academic year 2021-2022 as the sample used for the Table Tennis course and semester 2 of the even academic year. 2021-2022 which is used as a sample for the Aquatic I course. The research carried out includes a qualitative descriptive type which evaluates the implementation of limited face-to-face lectures for the Table Tennis course with Aquatic I through interviews and filling out questionnaires via Google Form. The results obtained from interviews for Table Tennis courses based on 1) indicators of the evaluation of the learning process concluded that most of the learning process could run well even though it was limited by health protocols 2) indicators of evaluation of the implementation process, it could be concluded that the process of implementing face-to-face lectures was limited to courses Table Tennis is quite good and 3) Based on the indicators of learning outcomes, it can be concluded that the learning outcomes can be achieved, although it must be improved in several supporting factors such as the internet network and the availability of table tennis which needs to be increased. While the results obtained from interviews for Aquatic I Course are based on 1) indicators of evaluation of the learning process, it can be concluded that most of the learning process can run well even though it is limited by health protocols 2) indicators of evaluation of the implementation process, it can be concluded that the process of implementing face-to-face lectures is limited by eyes. Aquatic I lecture is quite good and 3) Based on the indicators of learning outcomes, it can be concluded that learning outcomes can be achieved, although it must be improved in several supporting factors such as the internet network. The results obtained by filling out questionnaires for the Table Tennis Course show that the Table Tennis lectures were carried out well even though they were held face-to-face. The same results were obtained through filling out questionnaires for the Aquatic I Course, indicating that the Aquatic I lecture was carried out well even though it was held face-to-face in a limited manner. In conclusion, during limited face-to-face lectures, both Table Tennis and Aquatic I courses can be carried out well.